Brain Modulatory Effects by Low-Intensity Transcranial Ultrasound Stimulation (TUS): A Systematic Review on Both Animal and Human Studies - Wang, Pu; Zhang, Jiaqi; Yu, Jiadan; Smith, Colin; Feng, Wuwei (Frontiers in Neuroscience, 2019)
Abstract Background and objective: Low Intensity Transcranial Ultrasound Stimulation (TUS) is a new form of non-invasive brain modulation with promising data; however, systematic reviews on the brain modulatory effects of TUS on both animals and humans have not been well conducted. We aimed to conduct a systematic review on the studies using the TUS to modulate the brain functions and associated behavioral changes in both animals and humans. Methods: A literature search for published studies in the past 10 years was conducted. Two authors independently reviewed the relevant articles. Data were extracted and qualitatively summarized. Quality of studies was assessed by the SYRCLE’s risk of bias tool for preclinical studies or PEDro scale for clinical studies. Results: A total of 24 animal studies (506 animals) and 11 human studies (213 subjects) were included. Findings based on most animal studies demonstrated the excitatory or suppressive modulatory effects of ultrasonic stimulations on motor cortex, somatosensory cortex, thalamus, prefrontal cortex, auditory and visual areas. Brain modulatory effects also were found among healthy human subjects in seven studies and two clinical studies suggested TUS may result in potential benefits on patients with disorder of consciousness or chronic pain. The safety concerns of TUS seem to be minor based on the human studies. Conclusions: TUS appears to be a viable technique in modulating the brain functions; however, research on TUS is still in its early stages, especially in human studies. Parameters need to be optimized before launching systematic investigations in humans.